Predictors of a Minimal Clinically Important Difference Following Omalizumab Treatment in Adult Patients With Severe Allergic Asthma - Huang, Wei-Chang; Fu, Pin-Kuei; Chan, Ming-Cheng; Chin, Chun-Shih; Huang, Wen-Nan; Lai, Kuo-Lung; Wang, Jiun-Long; Hung, Wei-Ting; Wu, Yi-Da; Hsieh, Chia-Wei; Wu, Ming-Feng; Chen, Yi-Hsing; et al. (Frontiers in Medicine, 2022)
Several factors have been found to be predictors of a good response following omalizumab treatment in patients with severe allergic asthma (SAA). However, it remains unclear whether clinical characteristics can predict a minimal clinically important difference (MCID) following omalizumab treatment in this population. Therefore, the aim of this study was to investigate the features associated with an MCID following omalizumab treatment in adult patients with SAA. Of the 124 participants enrolled in this retrospective, cross-sectional study, 94, 103, 20 and 53 achieved the MCID following treatment with omalizumab and were considered to be responders of exacerbation reduction (no exacerbation during the one-year follow-up period or ≧50% reduction in exacerbations from baseline), oral corticosteroid (OCS) sparing (no use of OCS to control asthma during the study period or a reduction of the monthly OCS maintenance dose to <50% of baseline), lung function (an increase of ≧230 ml in the forced expiratory volume in one second from baseline) and asthma control (an increase of ≧3 points in the asthma control test score from baseline), respectively. Normal weight (<25 kg/m2 versus ≧30 kg/m2, odds ratio (OR)=3.86, p=0.024) was predictive of a responder of reduction in exacerbations following omalizumab treatment while subjects with a blood eosinophil level of <300 cells/μL (<300 cells/μL versus ≧300 cells/μL, OR=5.81, p=0.001) were more likely to exhibit an MCID in OCS sparing. No factor was found to be a predictor of lung function or asthma control. When choosing treatment for adult patients with SAA, our findings may help to select those who may benefit the most from omalizumab treatment.